2012
DOI: 10.1182/blood-2011-07-364992
|View full text |Cite
|
Sign up to set email alerts
|

Role and regulation of phosphatidylinositol 3-kinase β in platelet integrin α2β1 signaling

Abstract: Integrin ␣2␤1-mediated adhesion of human platelets to monomeric type I collagen or to the GFOGER peptide caused a time-dependent activation of PI3K and Akt phosphorylation. This process was abrogated by pharmacologic inhibition of PI3K␤, but not of PI3K␥ or PI3K␣. Moreover, Akt phosphorylation was undetectable in murine platelets expressing a kinase-dead mutant of PI3K␤ (PI3K␤ KD ), but occurred normally in PI3K␥ KD platelets. Integrin ␣2␤1 failed to stimulate PI3K␤ in platelets from phospholipase C␥2 (PLC␥2)-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
48
2
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
4
1

Relationship

2
7

Authors

Journals

citations
Cited by 61 publications
(62 citation statements)
references
References 46 publications
8
48
2
2
Order By: Relevance
“…47 In a recent study, we have also found that ex vivo thrombus formation under flow conditions on a collagen matrix was strongly reduced in the absence of Pyk2. 14 Our findings also indicate that Pyk2 is relevant, but not essential, for hemostasis because the bleeding time was mildly increased in Pyk2-KO mice. However, we observed a high variability in the time required to stop bleeding in the absence of Pyk2, and a clear bleeding tendency was observed in only approximately one-third of the analyzed mice.…”
Section: Org Fromsupporting
confidence: 56%
See 1 more Smart Citation
“…47 In a recent study, we have also found that ex vivo thrombus formation under flow conditions on a collagen matrix was strongly reduced in the absence of Pyk2. 14 Our findings also indicate that Pyk2 is relevant, but not essential, for hemostasis because the bleeding time was mildly increased in Pyk2-KO mice. However, we observed a high variability in the time required to stop bleeding in the absence of Pyk2, and a clear bleeding tendency was observed in only approximately one-third of the analyzed mice.…”
Section: Org Fromsupporting
confidence: 56%
“…[9][10][11][12][13] Phosphorylation of Pyk2 downstream of integrin ␣IIb␤3 and ␣2␤1 engagement has also been reported. 10,14 In thrombin-and VWF-activated platelets, Pyk2 interacts with the actin-based cytoskeleton. 9,11 Other studies have documented its association with PI3K, Cas, Shc, and Hic-5.…”
Section: Introductionmentioning
confidence: 99%
“…Activation of Pyk2-dependent signaling events appears to represent a bifurcation of TLR induced signaling as inhibitors of Src block the Pyk2-mediated responses without influencing IRAK-1-mediated signal transduction (51). Furthermore, Pyk2 has recently been shown to be critical for PI3KB integrin-mediated activation of platelet adhesion (57). However, there is likely cross talk between canonical TLR signaling and Pyk2-mediated signaling because Pyk2-deficient macrophages undergo reduced LPSinduced activation of NF-B and IL-1 expression (53).…”
Section: Discussionmentioning
confidence: 99%
“…This role of PI3K-β is in good agreement with the literature, demonstrating that this kinase is a major regulator of Akt phosphorylation and downstream integrin activation in response to various platelet agonists. 31,[41][42][43] Other authors have suggested that CD40L in platelets signals via p38 mitogen-activated protein kinase, 19 or via tyrosine phosphorylation of the integrin β 3 chain. 22 These pathways may coexist and help to support the establishment of platelet-platelet interactions.…”
Section: Apoementioning
confidence: 99%